Rights of transgender boys and girls in Ecuador - Flores Pillajo, Robert Enrique; Ruiz Abril, Karina; Cabrera Velez, Juan Pablo (Revista Universidad de Guayaquil, 2018)
The child or transgender girl refers to those who identify with the genre contrary to their sex; The rights of transgendered children in Ecuador are violated in view of the fact that their best interests do not prevail. Public policies and legal provisions in favor of transgender children are null and void in the Constitutional Rights Ecuador. The serious ignorance of the issue without inclusive education and information on gender dysphoria in boys and girls is a new reality in Ecuadorian society that translates into bullying with considerations of transphobia and presumably will lead to hate crimes against transgender children. Forcing them to live a childhood in total discontent because they are at odds with their biological sex bringing multiple psychological problems for them and their families that may even lead to suicide.
Keywords: Rights; boys; girls; transgender; gender; sex; good living; Higher interest; gender dysphoria